O fenômeno do cyberbullying em adultos e suas associações com indicadores de saúde mental e traços de personalidade - Lipp, Lauren Gonçalves de Sá (2021)
Studies on cyberbullying are increasingly important in the context in which we live. The Information and Communication Technologies - ICTs – increase has taken significant proportions allowing virtual violence common and in different contexts. The vast majority of studies on this topic assess risks in children and adolescents, and little attention has been given on cyberbullying in adulthood, and its possible risks. Different studies have already reported how this phenomenon affects those involved, regardless of the role they play in it. Symptoms related to low self-esteem, loneliness, sadness, and suicidal thoughts have already been related to involvement in cyberbullying situations. In order to better understand this model of cyberbullying in the adult population and understand the relationships with possible mental health outcomes and personality traits, this study analyzed these relationships, as well as descriptive data to better understand cyberbullying in Brazilian adults. The five-factor model of personality was also tested as well as mental health variables as anxiety, stress, and depression. To achieve this aim, an empirical study was conducted to verify if gender differences in different roles in cyberbullying, to understand the association between mental health indicators and the different roles in cyberbullying, and if there is association with the five personality factors and this kind of violence. In this sense, a sample of 237 adults, with ages between 18 and 65 years-old (mean age = 33.9 years) participated, through online survey, answering a questionnaire about technology use, cyberbullying scale, mental health indicator scale, and a brief inventory of the Five Personality Factors. The results indicated that in the adult population the same overlapping of roles found in the adolescent population is observed, and an important association between the roles of victim and aggressor was found, that is, the individual may be a perpetrator of virtual aggression and he/she may also be also a victim of these aggressions, acting as a bully-victim. The different roles presented positive associations with the three mental health indicators analyzed: anxiety, stress and depression. Neuroticism was the only personality factor associated with both victim and aggressor roles. Associations with the use of technology for leisure with the mental health variables were also found , and stress was considered, from an expected influence graph, to be the most influential variable in the model studied. The results of this study contribute to a better understanding of the phenomenon of cyberbullying in adulthood and its possible consequences, as well as open space to the promotion of protective contexts for the adults considering this virtual violence.